Impact of Artificial Intelligence in Education: Insights from Students and Faculty Members at Yarmouk University - Ghalia, Nadia; Isami, Eyal; bsoul, miriam; Aabed, Saierah.; haeb, Rema salh; Mustafa, Mawaheb (Journal of Ecohumanism, 2024)
The landscape of education is undergoing a gradual transformation due to Artificial Intelligence (AI), which is revolutionizing learning and teaching methods. Using Yarmouk UniversityAr as a case study, this study investigates perceptions and impacts of AI within educational contexts. Students and faculty members from a variety of backgrounds participated in the cross-sectional survey. A survey focused on familiarity, perceived advantages, and potential challenges associated with AI in education was administrated to a sample of (387) students and (23) faculty members.According to the results, attitudes and awareness levels regarding artificial intelligence differed significantly between the groups surveyed. In particular, 66.7% of students appreciated AI’s ability to enhance lessons and foster personalized learning experiences. Faculty members, however, expressed more caution, with 50% of them expressing concerns about the dehumanization of education and security issues related to student data while recognizing the positive impact.